PATHOMORPHOLOGICAL STATE OF LIVER TISSUES IN RATS WITH EXPERIMENTAL METABOLIC SYNDROME WITH QUERCETIN CORRECTION - Frenkel, Yu.D.; Cherno, V.S.; Zyuzin, V.O.; Pshychenko, V.V.; Starchenko, I.I.; Kostenko, V.O.; Stepanchuk, A.P. (World of Medicine and Biology, 2023)
Using an experimental model, we studied the features of the state of the rat’s liver tissues under the conditions of experimental metabolic syndrome with quercetin correction. Features of the state of tissues and their morphometric characteristics were microscopically determined in semi-thin histological sections. The majority of hepatocytes visually did not differ from those in the control group and were characterized by a polygonal shape with distinct contours. Hepatic cells with necrotic changes were not detected. Hepatocytes with signs of fatty dystrophy, in which osmiophilic inclusions were present in the cytoplasm, were periodically encountered. In general, sinusoidal capillaries contained some blood corpuscles, some moderately dilated. Although the cross-sectional area of hepatocytes decreased compared to the previous experimental group without correction, it remained larger compared to intact animals. The area of the cytoplasm of liver cells also decreased significantly. The cross-sectional area of the hepatocyte nucleus did not differ much from the previous experimental group. Accordingly, the nuclear-cytoplasmic ratio significantly increased in hepatocytes after quercetin correction, but was lower compared to intact animals. An increase in the number of mononuclear hepatocytes, which practically did not differ from the corresponding indicator in intact animals, should also be considered a morphological manifestation of the protective action of the polyphenol Quercetin in metabolic syndrome.